PENERAPAN STRATEGI PEMBELAJARAN THINK TALK WRITE (TTW) DENGAN AUTHENTIC ASSESSMENT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PADA SUB-POKOK BAHASAN LOGIKA MATEMATIKASISWA KELAS X SMA NEGERI 1 TANGGUL JEMBER SEMESTER GENAP TAHUN AJARAN 2011/2012 - Rahman, Nikita; Sugiarti, Titik; Suharto, S (Department of Mathematics Education , University of Jember, 2013)
Abstract. The learning strategy is one of cause influenced the student’s learning completion. It means that to reach high teaching quality, all studies, especially math, should be organized with the right organizing strategy, then explained to the students with the right strategy. One of the learning strategy which make the students learning desire grow by activating all student’s potential in visual, auditory, or kinesthetic were think talk write learning strategy with authentic assessment. The type of this research was classroom action research. The research aimed to find out the student’s activity, student’s learning completeness, and student’s respond to think talk write learning strategy. While the objects were students of X-1 Grade SMAN (Junior High School) 1 Tanggul Jember Residence with 40 students amount. The results of applied research after think talk write learning strategy with authentic assessment the average student in the first cycle with 82 reaching 92,5% completeness, where there are 37 students who completed and 3 students did not complete. Then proceed to the second round, second round results on the average value of 84,75 students to reach 100% completeness. Based on the success criteria for this study that at least 75% of the entire class of students there is scored 75-100 or completeness reach 75% -100%. Therefore, it is associated with learning the completeness criteria, the results of this study meets these criteria. It can be concluded that the application of think talk write learning strategy with authentic assessment can improve student learning outcomes in math study in SMAN (Junior High School) 1 Tanggul Jember. Key Words : Think Talk Write Learning strategy, Aunthentic Assessment, Student’s Learning Completeness, Learning Strategy, Think Talk Write Implementation.